Neuromorphological and Neurofunctional Correlates of ADHD and ADD in the Auditory Cortex of Adults - Serrallach, Bettina L.; Groß, Christine; Christiner, Markus; Wildermuth, Simon; Schneider, Peter (Frontiers in Neuroscience, 2022)
Attention deficit (hyperactivity) disorder (AD(H)D) is one of the most common neurodevelopmental disorders in children with up to 60% probability of prevailing into adulthood. AD(H)D has far-fetching negative impacts on various areas of life. Until today, no observer-independent diagnostic biomarker is available for AD(H)D, however recent research found evidence that AD(H)D is reflected in auditory dysfunctions. Furthermore, the official diagnostic classification systems, being mainly the ICD-10 in Europe and the DSM-5 in the United States, are not entirely consistent. The neuro-auditory profiles of 82 adults (27 ADHD, 30 ADD, 25 controls) were measured via structural magnetic resonance imaging (MRI) and magnetoencephalography (MEG) to determine gray matter volumes and activity of auditory subareas [Heschl’s gyrus (HG) and planum temporale (PT)]. All three groups (ADHD, ADD, and controls) revealed distinct neuro-auditory profiles. In the left hemisphere, both ADHD and ADD showed reduced gray matter volumes of the left HG, resulting in diminished left HG/PT ratios. In the right hemisphere, subjects with ADHD were characterized by lower right HG/PT ratios and ADD by a similar right HG/PT ratio compared to controls. Controls and ADD had well-balanced hemispheric response patterns, ADHD a left-right asynchrony. With this study, we present the structural and functional differences in the auditory cortex of adult patients with AD(H)D.